Walls, wisdom, worries, and wishes: Engaging communities in discussion about death, dying, loss, and care using Café Conversation. (2nd January 2016) - McLoughlin, K.; McGilloway, S.; Lloyd, R.; O'Connor, M.; Rhatigan, J.; Shanahan, M.; Richardson, M.; Keevey, A.
Abstract : This paper reflects on the adaptation of the World Café concept to engage with members of the public in Compassionate Communities Café Conversation, focussing on enabling people to understand the importance of thinking and talking about the end of life. The approach enables people to come together to share their experience and ideas, wisdom, worries, and wishes. The seven design principles of the World Café are central to the process, together with the sharing of resources developed to engage people in discussion as well as practical activity. This paper outlines the preparation, presentation, and pilot evaluation of the Compassionate Communities Café Conversation experience in two towns in the Mid-West of Ireland. The experience and findings suggest that this approach offers a potentially very useful framework for use by others as part of a health promoting approach to palliative care.